2014
DOI: 10.7717/peerj.585
|View full text |Cite
|
Sign up to set email alerts
|

Culture-independent detection and characterisation ofMycobacterium tuberculosisandM. africanumin sputum samples using shotgun metagenomics on a benchtop sequencer

Abstract: Tuberculosis remains a major global health problem. Laboratory diagnostic methods that allow effective, early detection of cases are central to management of tuberculosis in the individual patient and in the community. Since the 1880s, laboratory diagnosis of tuberculosis has relied primarily on microscopy and culture. However, microscopy fails to provide species- or lineage-level identification and culture-based workflows for diagnosis of tuberculosis remain complex, expensive, slow, technically demanding and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 58 publications
2
63
0
Order By: Relevance
“…An alternative and cheaper rapid sequencing-based approach would be to perform deep sequencing of total DNA from sputum samples without enrichment. The authors of a recent study found they could recover M. tuberculosis reads from eight smear-and culturepositive samples (34). However, in agreement with our study, they obtained a very low (Ͻ1ϫ) depth of coverage in the absence of enrichment, so the usefulness of this approach is likely to be limited to detection and it is unlikely to provide the detailed genotype and resistance information that is presented here in a highthroughput manner.…”
Section: Discussionsupporting
confidence: 85%
“…An alternative and cheaper rapid sequencing-based approach would be to perform deep sequencing of total DNA from sputum samples without enrichment. The authors of a recent study found they could recover M. tuberculosis reads from eight smear-and culturepositive samples (34). However, in agreement with our study, they obtained a very low (Ͻ1ϫ) depth of coverage in the absence of enrichment, so the usefulness of this approach is likely to be limited to detection and it is unlikely to provide the detailed genotype and resistance information that is presented here in a highthroughput manner.…”
Section: Discussionsupporting
confidence: 85%
“…Further, in a proof-of-principle study, the same process was used to identify and characterize pathogenic mycobacteria in modern sputum samples (48)(49)(50). There have been several other recent proof-of-principle studies that demonstrate the utility of this diagnostic approach (13,15,51,52).…”
Section: The Role Of Clinicogenomics In Public Health Microbiologymentioning
confidence: 99%
“…Metagenomics as a diagnostic approach is likely to move closer to routine practice (Loman et al ., 2013; Doughty et al ., 2014; Pallen, 2014; Wilson et al ., 2014), but reliably disentangling pathogen genomes from metagenomes – particularly if short‐read technologies still dominate the field – is going to present a formidable challenge (Alneberg et al ., 2014). …”
mentioning
confidence: 99%